Site‐Selective and van der Waals Epitaxial Growth of Rhenium Disulfide on Graphene. Issue 2 (11th December 2018) - Seo, Jihyung; Lee, Junghyun; Jeong, Gyujeong; Park, Hyesung
Abstract: The surface property of growth substrate imposes significant influence in the growth behaviors of 2D materials. Rhenium disulfide (ReS2 ) is a new family of 2D transition metal dichalcogenides with unique distorted 1T crystal structure and thickness‐independent direct bandgap. The role of growth substrate is more critical for ReS2 owing to its weak interlayer coupling property, which leads to preferred growth along the out‐of‐plane direction while suppressing the uniform in‐plane growth. Herein, graphene is introduced as the growth substrate for ReS2 and the synthesis of graphene/ReS2 vertical heterostructure is demonstrated via chemical vapor deposition. Compared with the rough surface of SiO2 /Si substrate with dangling bonds which hinders the uniform growth of ReS2, the inert and smooth surface nature of graphene sheet provides a lower energy barrier for migration of the adatoms, thereby promoting the growth of ReS2 on the graphene surface along the in‐plane direction. Furthermore, patterning of the graphene/ReS2 heterostructure is achieved by the selective growth of ReS2, which is attributed to the strong binding energy between sulfur atoms and graphene surface. The fundamental studies in the role of graphene as the growth template in the formation of van der Waals heterostructures provide better insights into the synthesis of 2D heterostructures. Abstract : Vertical van der Waals heterostructure of graphene/rhenium disulfide (ReS2 ) is synthesized by chemical vapor deposition. The rhenium disulfide is successfully grown along the in‐plane direction on an atomically smooth and chemically inert graphene surface without developing any structural defects, resulting in the high‐quality graphene/rhenium disulfide heterostructure. In addition, the patterning of vertical heterostructure is achieved through the site‐specific growth of ReS2 .